The vampire ate my homework - Miedoso, Andres (Miedoso, Andres. Desmond Cole ghost patrol, 2021)
"Kersville Elementary School has a problem: there's a very hungry vampire on the loose! But this creature doesn't thirst for blood. Instead, he's been eating the students' homework! Can Desmond Cole stop the monster from turning everyone's work into food for thought?"--